Sickle Cell Disease: Reference Values and Interhemispheric Differences of Nonimaging Transcranial Doppler Blood Flow Parameters - Arkuszewski, M.; Krejza, J.; Chen, R.; Kwiatkowski, J.L.; Ichord, R.; Zimmerman, R.; Ohene-Frempong, K.; Desiderio, L.; Melhem, E.R. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: TCD screening is widely used to identify children with SCD at high risk of stroke. Those with high mean flow velocities in major brain arteries have increased risk of stroke. Thus, our aim was to establish reference values of interhemispheric differences and ratios of blood flow Doppler parameters in the tICA, MCA, and ACA as determined by conventional TCD in children with sickle cell anemia. MATERIALS AND METHODS: Reference limits of blood flow parameters were established on the basis of a consecutive cohort of 56 children (mean age, 100 ± 40 months; range, 29–180 months; 30 females) free of neurologic deficits and intracranial stenosis detectable by MRA, with blood flow velocities <170 cm/s by conventional TCD. Reference limits were estimated by using tolerance intervals, within which are included with a probability of .90 of all possible data values from 95% of a population. RESULTS: Average peak systolic velocities were significantly higher in the right hemisphere in the MCA and ACA (185 ± 28 cm/s versus 179 ± 27 and 152 ± 30 cm/s versus 143 ± 34 cm/s respectively). Reference limits for left-to-right differences in the mean flow velocities were the following: −43 to 33 cm/s for the MCA; −49 to 38 cm/s for the ACA, and −38 to 34 cm/s for the tICA, respectively. Respective reference limits for left-to-right velocity ratios were the following: 0.72 to 1.25 cm/s for the MCA; 0.62 to 1.39 cm/s for the ACA, and 0.69 to 1.27 cm/s for the tICA. Flow velocities in major arteries were inversely related to age and Hct or Hgb. CONCLUSIONS: The study provides reference intervals of TCD flow velocities and their interhemispheric differences and ratios that may be helpful in identification of intracranial arterial stenosis in children with SCD undergoing sonographic screening for stroke prevention. ACAanterior cerebral arteryCHOPChildren's Hospital of PhiladelphiaFSnedecor ratioHcthematocrit level (%)Hgbhemoglobin concentration (g/dL)ICAinternal carotid arteryMCAmiddle cerebral arteryMRAMR angiographyPIpulsatility indexrPearson correlationRSpearman correlationSCDsickle cell diseaseTCDtranscranial Doppler sonographytICAterminal segment of internal carotid arteryTOFtime-of-flightVEDend-diastolic velocityVMNmean time-averaged maximum velocityVPSpeak systolic velocity